COVID-19 and U.S.-China Relations
IX, 185 p. 23 illus., 18 illus. in color.
Keywords: This open access book offers a groundbreaking examination of the profound and lasting impacts of COVID-19 on U.S.-China relations. As the first comprehensive study on this topic, this book explores the multifaceted effects of COVID-19 on key aspects of U.S.-China relations, covering areas such as public health, trade and supply chain challenges, people-to-people connections, shifts in public opinion, rising nationalism, anti-Asian sentiments, and strategic assessments. Since the pandemic’s outbreak in late 2019, China and the United States have both suffered catastrophically. So too has the U.S.-China relationship, which was already at a historic low point before COVID-19 accelerated its deterioration. This book critically analyzes how the pandemic has deepened existing fissures and created new areas of tensions. Emphasizing the need for objective analysis, it underscores the importance of in-depth reflections on the pandemic and its far-reaching consequences, a crucial step towards healing and restoration in the post-COVID era. Beyond the direct impact on trade and bilateral relations, this book explores the wider social and political consequences of the pandemic. It examines how this public health crisis has shaped mutual understanding and perceptions between the two nations, stimulated the rise of nationalism and populism in both societies, and discusses how politicians have unfortunately exploited this crisis for political mobilization. With contributions by leading and emerging scholars from both nations, this book reflects a collaborative effort, emphasizing the importance of bilateral dialogue. As the world steps into the post-COVID era, this work offers timely insights into the potential pathways for rebuilding and redefining U.S.-China relations. Zheng Wang is the Director of the Center for Peace and Conflict Studies (CPCS) and Professor in the School of Diplomacy and International Relations at Seton Hall University. He has been the Boeing Visiting Chair at the Schwarzman College of Tsinghua University, an Abe Fellow of the Social Science Research Council, and a member of the National Committee on U.S.-China Relations. His book Never Forget National Humiliation received International Studies Association’s book award. .